Experimental Study on Unidirectional Pedestrian Descending and Ascending Stair With a Fixed Obstacle - Shi, Dongdong; Yang, Meicheng; Chen, Juan; Ma, Jian (Collective Dynamics, 2022)
Staircase is one of the most essential vertical passageway for pedestrians’ timely evacuation, and has distinct constraint on pedestrians’ movement characteristics when compared with corridors and hallways. During evacuation, temporary obstacles can be observed on stairs, e.g., the abruptly stopped pedestrians or the luggage of pedestrians discarded. It is noticed that studies on the effect of obstacles on pedestrian dynamics mainly focused on planar locomotion, the impact of obstacle on the movement characteristics of pedestrians ascending and descending stairs have not been systematically studied yet. Therefore, in this study, a series of unidirectional pedestrian avoid obstacle movement experiments on staircase under controlled laboratory conditions were performed. The avoidance characteristic of pedestrians is observed from trajectory diagram. Target drift angle towards left and right is further calculated and analyzed. The study found that target drift angle curve occur to relatively large fluctuations to avoid obstacle of a pedestrian rather than not appear to obvious variety to avoid obstacle of a suitcase. Meanwhile, the change trend of target drift angle towards left and right for scenarios S3 and S4 is consistent with results of scenarios S1 and S2. Then, an interesting discovery indicates that the pedestrians will accelerate after passing obstacles whether it is ascending process or descending process. Finally, the obstacle of a pedestrian will accelerate the movement efficiency in ascending process from results of flow rates, but the result is contrary to that of descending process. The systematic experimental data can not only be used for the verification and validation of pedestrian models but also can provide a benchmark for the design of related facilities aiming at improving traffic efficiency.